2021
DOI: 10.1007/s00426-021-01595-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hyperarticulation on speech comprehension under adverse listening conditions

Abstract: Comprehension assesses a listener’s ability to construe the meaning of an acoustic signal in order to be able to answer questions about its contents, while intelligibility indicates the extent to which a listener can precisely retrieve the acoustic signal. Previous comprehension studies asking listeners for sentence-level information or narrative-level information used native listeners as participants. This is the first study to look at whether clear speech properties (e.g. expanded vowel space) produce a clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…One possible explanation for the high performance of naive listeners in these conditions is that our stimuli were elicited to a non-native Tashlhiyt listener. Indeed, prior work has shown that non-native-directed speech is better perceived by both native and non-native listeners (Kangatharan et al, 2022). While the present study looked only at non-native directed speech, an avenue for future work is to investigate how clear speech patterns vary across different types of listeners and with different types of instructions.…”
Section: Discussionmentioning
confidence: 93%
“…One possible explanation for the high performance of naive listeners in these conditions is that our stimuli were elicited to a non-native Tashlhiyt listener. Indeed, prior work has shown that non-native-directed speech is better perceived by both native and non-native listeners (Kangatharan et al, 2022). While the present study looked only at non-native directed speech, an avenue for future work is to investigate how clear speech patterns vary across different types of listeners and with different types of instructions.…”
Section: Discussionmentioning
confidence: 93%
“…This study had two parts: a speech production experiment to elicit spontaneous speech produced when doing a 'Spot the Difference' task with different types of interlocutors as described previously in Kangatharan et al (2021), and a perceptual evaluation experiment using target words extracted from the speech production experiment. Both the speech production experiment and the perceptual evaluation experiment were approved by the Ethics committee at the Psychology Department at Brunel University.…”
Section: Methodsmentioning
confidence: 99%
“…This speech production experiment was conducted in a previous study (Kangatharan et al, 2021), and details are reported again here in the present study to describe how the speech tokens used for the speech perception experiment were obtained. The speech production experiment used a 2 (interlocutor's accent: native, foreign) × 2 (interlocutor's physical appearance: native, foreign) × 3 (three target vowels: /a:/, /uː/ and /iː/) mixed design with four different types of interlocutors: NLNS (native-looking and native-sounding), NLFS (native-looking and foreign-sounding), FLNS (foreign-looking and native-sounding), and FLFS (foreign-looking and foreign-sounding).…”
Section: Speech Production Experimentsmentioning
confidence: 99%
See 2 more Smart Citations